2021
DOI: 10.1051/0004-6361/202039590
|View full text |Cite
|
Sign up to set email alerts
|

The Abell 3391/95 galaxy cluster system

Abstract: Context. Inferences about dark matter, dark energy, and the missing baryons all depend on the accuracy of our model of large-scale structure evolution. In particular, with cosmological simulations in our model of the Universe, we trace the growth of structure, and visualize the build-up of bigger structures from smaller ones and of gaseous filaments connecting galaxy clusters. Aims. Here we aim to reveal the complexity of the large-scale structure assembly process in great detail and on scales from tens of kil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 118 publications
4
23
0
Order By: Relevance
“…These large groups can be treated as cluster-like systems with their own filament networks which will eventually merge with the more massive cluster. In Kuchner et al (2020) we have shown that these second most massive halos (SMH) are connected to the central clusters with thick bridges, as has also been described in numerous observations (e.g., Durret et al 2008;Tanimura et al 2019;Umehata et al 2019;Reiprich et al 2021).…”
Section: Scatter On the Extremessupporting
confidence: 73%
“…These large groups can be treated as cluster-like systems with their own filament networks which will eventually merge with the more massive cluster. In Kuchner et al (2020) we have shown that these second most massive halos (SMH) are connected to the central clusters with thick bridges, as has also been described in numerous observations (e.g., Durret et al 2008;Tanimura et al 2019;Umehata et al 2019;Reiprich et al 2021).…”
Section: Scatter On the Extremessupporting
confidence: 73%
“…Early EMU/eROSITA results on the Abell 3391/95 galaxy cluster system (Reiprich et al 2021;Brüggen et al 2021) have already helped constrain physical processes in the merger. We show two additional examples of diffuse radio sources detected in the EMU-PS area in Figures 33 and 34.…”
Section: Clusters Of Galaxiesmentioning
confidence: 99%
“…There have been few direct detections of hot gas filaments in the X-ray (Werner et al 2008;Eckert et al 2015), as well as a recent E-mail: tessa.vernstrom@csiro.au detection via stacking (Tanimura et al 2020). The most recent direct detection from Reiprich et al (2021) used the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) telescope to measure a 15 Mpc long X-ray filament between two clusters. These studies suggest temperatures of order 10 5 -10 7 K, densities of 10-100 times the average cosmic value and about 5-10 per cent of their mass in baryonic gas.…”
mentioning
confidence: 99%